Longitudinal changes in quantitative magnetic resonance imaging metrics in children and young adults with autoimmune liver disease. - Mahalingam, Neeraja; Trout, Andrew T.; Zhang, Bin; Castro-Rojas, Cyd; Miethke, Alexander G.; Dillman, Jonathan R. (Abdominal Radiology, 2023)
Purpose: To assess longitudinal changes in quantitative MRI metrics in pediatric and young adult patients with autoimmune liver disease (AILD). Methods: This prospective, IRB-approved study included 20 children and young adults (median age = 15 years) with primary sclerosing cholangitis (PSC)/autoimmune sclerosing cholangitis (ASC) and 19 (median age = 17 years) with autoimmune hepatitis (AIH). At a field strength of 1.5-T, T2*-corrected T1 mapping (cT1), 3D fast spin-echo MRCP, and 2D gradient recalled echo MR elastography (MRE) were performed at baseline, one year, and two years. cT1 and quantitative MRCP were processed using LiverMultiScan and MRCP + , respectively (Perspectum Ltd, Oxford, UK). Linear mixed models were used to assess longitudinal changes in quantitative MRI metrics. Spearman rank-order correlation was used to assess relationships between changes in quantitative MRI metrics. Results: Changes in quantitative MRI metrics greater than established repeatability coefficients were measured in six (cT1) and five (MRE) patients with PSC/ASC as well as in six patients (cT1 and MRE) with AIH, although linear mixed models identified no significant changes for the subgroups as a whole. For PSC/ASC, there were positive correlations between change in liver stiffness and changes in bile duct strictures (ρ = 0.68; p = 0.005) and bile duct dilations (ρ = 0.70; p = 0.004) between baseline and Year 2. Conclusion: On average, there were no significant changes in quantitative MRI metrics over a two-year period in children and young adults with AILD. However, worsening cholangiopathy was associated with increasing liver stiffness by MRE in patients with PSC/ASC.